SISTEM INFORMASI PERSEDIAAN BARANG SECARA MULTIUSER PADA APOTIK KINASIH BULU SUKOHARJO DENGAN METODE RATAâ€“RATA BERGERAK - Wawan Laksito YS, Ndaru Mardi Pranggono, Tri Irawati, (Jurnal Ilmiah SINUS, 2016)
Pharmacies Kinasih is a company engaged in the sale of medicine. Competition and sales as the main reason for Pharmacies Kinasih in developing information systems in order to improve the supply of products and presentation of data at the warehouse at the moment is not done manually but using a service-based information system so that the accuracy and the necessary information to provide convenience to the inside provide a report with precise and fast. The moving average method is a system where the card inventory and cost of goods per unit of inventory is always changing every happening purchase new items with moving average Equity Cost of goods sold if there is a subsequent change in the purchase price. With the moving average method can easily determine the price of goods sold in case of price increases and price declines so that no more profits and losses. System information that is created by using visual basic.Net generate output report goods data, supplier data reports, purchasing reports, reports purchase returns, sales reports, sales reports with recipes, statement items, inventory reports, report card stock, report average moving average, stock report hospitalization.Â Keywords: Information Systems, Method Average - Moving Average, Inventory